1993
DOI: 10.1093/carcin/14.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate on DNA content, glutathione S-transferase activities, cell morphology and growth characteristics of rat liver nonparenchymal epithelial cells in vitro

Abstract: The effects of sodium butyrate, which has been shown to act as a differentiation promoting agent in several different tumor cell lines, were studied in a rat liver nonparenchymal epithelial cell line. Exposure of these cells to 3.75 mM butyrate resulted in an inhibition of cell proliferation and, at the same time, an increase in cell diameter (2-to 6-fold) and size of the nuclei (~ 2-fold) after 3 days in culture. Binucleated cells arose, comprising ~ 12% of the cells investigated, and the number of cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Nevertheless, butyrate may also act as co-mutagen, since we present evidence that the induction of cell dierentiation by butyrate attenuates p53-dependent DNA damage response. Co-mutagenic features (Sankaranarayanan et al, 1984;Hojo et al, 1994), even a direct mutagenic eect of butyrate (Utesch et al, 1993), are reported by others. Both, anti-neoplastic and co-carcinogenic in vitro eects of butyrate may be correlated to in vivo observations, as epidemiological studies suggest an important role of butyrate in the prevention of colorectal cancer (Stemmermann and Yatani, 1972;Howe et al, 1992).…”
Section: Concentration Of Butyratementioning
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, butyrate may also act as co-mutagen, since we present evidence that the induction of cell dierentiation by butyrate attenuates p53-dependent DNA damage response. Co-mutagenic features (Sankaranarayanan et al, 1984;Hojo et al, 1994), even a direct mutagenic eect of butyrate (Utesch et al, 1993), are reported by others. Both, anti-neoplastic and co-carcinogenic in vitro eects of butyrate may be correlated to in vivo observations, as epidemiological studies suggest an important role of butyrate in the prevention of colorectal cancer (Stemmermann and Yatani, 1972;Howe et al, 1992).…”
Section: Concentration Of Butyratementioning
confidence: 68%
“…Simultaneously with cell dierentiation in response to butyrate, bi-and multinucleated cells arose. Others observed not only multinucleated cells, but also abnormal sets of chromosomes during exposure to butyrate (Utesch et al, 1993). Both, multinucleated cells and chromosomal abnormalities, also occur in vivo in p53 knockout mice (Cross et al, 1995;Bouer et al, 1995).…”
Section: Concentration Of Butyratementioning
confidence: 98%
“…RA and NaB produce similar effects in other in vitro culture systems (Toscani et al 1988, Staiano-Coico et al 1990, De Luca 1991, Rocchi et al 1992, Utesch et al 1993, Lopez-Boado et al 1994, Saito et al 1994, Borge et al 1996, Peverali et al 1996. What is rather surprising is the lack of effects of RA treatment on our cells, because retinoids and some of their receptors have been recognized, long ago, to have major effects on cell proliferation and differentiation, and they have also been implicated in the regulation of PCD both in vivo during embryo development and in vitro in many normal or transformed cell lines (Lotan 1990, De Luca 1991, Linney 1992, Lopez-Boado et al 1994, Zhang et al 1995, Peverali et al 1996, Spanjaard et al 1997.…”
Section: Discussionmentioning
confidence: 84%
“…Butyrate-induced differentiation was also observed in several types of transformed cells (Kruh 1982) and was usually associated with growth arrest (Staiano-Coico et al 1990, Rocchi et al 1992, Utesch et al 1993. Several studies have demonstrated that, in other in vitro culture systems, NaB induces growth arrest followed by apoptosis, rather than differentiation (Hague et al 1995, Soldatenkov et al 1998.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation